Information environment quantifiers as investment analysis basis - Dmitry G. Rodionov; Polina A. Pashinina; Evgenii A. Konnikov; Olga A. Konnikova (Economies, 2022)
The combination of the processes of widespread digitalization and globalization of the world economy has led to a significant expansion of the global information environment. The modern information environment is dynamically active, and changes in it are indicators of changes in the material world. This specificity can be used for investment analysis purposes. However, at the time of this research, a universal methodology for analyzing the information environment has not yet been formed. The purpose of this study is to develop tools for quantifying the information environment and testing them as investment predictors. The key result of this study is a stock price forecasting model based on information environment quantifiers and its critical analysis. The results obtained will be useful both for investors of different skill levels and for researchers of the information environment.
Keywords: 330; financial market; information environment; quantification; tokenization; tonality